Serum visfatin levels in non-obese women with polycystic ovary syndrome and matched controls - Jin Ju Kim; Young Min Choi; Min A Hong; Min Jeong Kim; Soo Jin Chae; Sun Mie Kim; Kyu Ri Hwang; Sang Ho Yoon; Seung Yup Ku; Chang Suk Suh; Seok Hyun Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThe purpose of the current study was to compare the circulating levels of visfatin between women with polycystic ovary syndrome (PCOS) and those without PCOS and to assess the correlations between visfatin levels and various parameters.MethodsThis case-control study recruited 74 PCOS patients and 74 age- and body mass index (BMI)-matched controls. Serum visfatin levels were evaluated using the enzyme-linked immunosorbent assay. Women with PCOS were divided into 2 subgroups based on the presence of clinical or biochemical hyperandrogenism. The possible differences in serum visfatin levels between the hyperandrogenic and non-hyperandrogenic groups were also assessed.ResultsVisfatin levels in PCOS patients were similar to those in the controls. However, hyperandrogenic patients had significantly higher mean serum visfatin levels than those in non-hyperandrogenic patients (3.87 ng/mL; 95% confidence intervals [CIs], 3.09-4.85 in hyperandrogenic group vs. 2.69 ng/mL; 95% CIs, 2.06-3.52 in non-hyperandrogenic group; P=0.038). In women with PCOS, visfatin levels positively correlated with BMI (r=0.23; P=0.047) and the log free androgen index (FAI) (r=0.27; P=0.021) and negatively correlated with high-density lipoprotein (HDL) cholesterol levels (r=−0.37; P=0.025). Except for HDL cholesterol levels, these correlations were also observed in controls.ConclusionVisfatin levels in PCOS patients were similar to those in the controls. However, hyperandrogenic patients showed significantly higher serum visfatin levels than those of non-hyperandrogenic patients, and visfatin had a positive linear correlation with FAI in both PCOS patients and controls.